호산구증다증과 동반된 비삽화성 혈관부종의 1예 - 최지웅; 박소영; 문경태; 이원미; 이병훈; 김상훈 (Allergy asthma & respiratory disease, 2021)
Nonepisodic angioedema with eosinophilia (NEAE) is a rare disease characterized by nonrecurrent angioedema with eosinophilia and normal serum IgM levels occurring predominantly in an East Asian female population. A 49-year-old male patient visited our clinic due to swelling of both the scrotums and the lower extremities, and fever. He had history of nasal polyp, cephalosporin allergy, and asthma. He was diagnosed as having NEAE and was treated with systemic corticosteroid, then he was symptom-free for more than 8 months. He had been administered omalizumab for 3 months due to uncontrolled asthma prior to the onset of angioedema which had helped taper the oral corticosteroid, and this may be associated with presentation of NEAE. Here, we report a case of NEAE in a male patient which presented with constitutional symptoms such as fever and scrotal edema. KCI Citation Count: 0